Case Report: Meningoencephalomyelitis of unknown origin in foxes (Vulpes vulpes and Vulpes lagopus): insights into the diagnostic challenges in carnivore neurology - Steiner, Natalie; Dembowski, Martin; Moeselaken, Florian Richard; Mirolo, Monica; Ludlow, Martin; Dierig, Julie-Ann; Mikić, Manon; Watanangura, Antja; Ulrich, Reiner; Puff, Christina; Pees, Michael; Nessler, Jasmin Nicole (Frontiers in Veterinary Science, 2025)
Emerging diseases in wildlife pose significant diagnostic challenges, with increasing evidence that not all cases of inflammatory disease can be directly attributed to infectious pathogens. This case series shows the results of clinical examination, magnetic resonance imaging, and necropsy results of two foxes, a silver fox (Vulpes vulpes) and a polar fox (Vulpes lagopus), with non-suppurative meningoencephalomyelitis. Extensive diagnostics, including pathogen screening and next-generation sequencing, failed to identify a definitive causative infectious agent. These cases suggest the possibility of an immunopathologic disease, highlighting the need for immunological assessments in wildlife disease investigations.